Behavioural and skill-based early interventions in children with autism spectrum disorders - Weinmann, Stefan (German Medical Science GMS Publishing House, 2009)
INTRODUCTION: Autism spectrum disorders (ASD) comprise typical or infantile autism (Kanner syndrome), Asperger’s disorder and atypical autism or pervasive developmental disorder - not otherwise specified. The syndrome is characterized by deficits in (1) verbal and nonverbal communication, (2) reciprocal social interaction and (3) repetitive patterns of behaviour, interests and activities. Early behavioural interventions are based on learning theory and behaviour therapy. They take into account specific deficits in perception, emotional reactions, social interaction and communication. In Germany, these comprehensive models are not widely evaluated and implemented. RESEARCH QUESTIONS: What are the clinical effectiveness and safety of early behavioural or skills-based early interventions in autism compared to other interventions or to treatment as usual? What are specific factors responsible for the effectiveness? What are the cost-effectiveness and cost consequences of different early interventions in autism? Which legal, social and ethical aspects are relevant with regard to the implementation of the respective interventions in persons with autism? METHODS: Following a systematic review of the literature, controlled studies on early behavioural or skills-based interventions published since 2000 in English or German with children until the age of twelve are included and critically appraised. Studies must have at least ten participants per intervention group. RESULTS: In total, 15 publications based on 14 studies, eight systematic reviews and one health economic study are included. Most studies evaluate early interventions based upon the Lovaas model (Early intensive behavioural treatment (EIBT), Applied behavioural analysis (ABA)). Other evaluate pragmatic interventions or interventions based on other theoretical models like specific parent interventions, responsive education and prelinguistic milieu teaching, joint attention, symbolic play, and picture exchange communication system. Behaviour analytic interventions referring to the Lovaas model remain the most empirically evaluated early interventions in autism. Preschool children with autism can achieve improvements in cognitive and functional domains when treated within behavioural interventions with a frequency of at least 20 hours per week. It is not clear which is the minimum duration of effective interventions, and which active components are necessary for the effectiveness. There was no high quality evidence for other comprehensive early interventions. The identified health economic study is not suitable to evaluate the cost-effectiveness or cost consequences of early interventions. No publications concerning legal, ethical or social aspects were identified. The financial situation of persons with autisms and their families will be improved through the implementation of the “Pflege-Weiterententwicklungsgesetz” (Pf-WG). Further questions concern the organisation of care and the legal representation of autistic patients. Ethical questions arise mainly in the context of the equal supply of care to each individual patient in all regions of the country and the situation of the caregivers. DISCUSSION: There are only a few studies with high methodology evaluating early interventions in children with autism. Most studies have a short duration with a lack of blinded outcome assessment in many cases. The lack of high quality comparative studies does not allow answering questions of comparative effectiveness of early interventions in autism. It can be concluded that interventions referring to the Lovaas model seem to have the highest effectiveness. This seems to be especially true when they are run clinic-based. However, there was no solid evidence with regard to factors responsible for the effectiveness of programms according to the ABA model. With regard to communication improvement, a systematic parent training seems to be superior to treatment as usual where a mixture of therapeutic elements is used. As well for clinical and health economic studies there is a substantial problem of generalisability into the German context. The identified health economic study is not suitable to evaluate the cost-effectiveness or cost consequences of early interventions. CONCLUSION: Based on the available studies, there is no sufficient evidence for any of the evaluated behavioural early intervention programmes. Studies suggest that preschool children with autism in behavioural intervention programmes with a frequency of at least 20 hours per week can achieve improvements in cognitive and functional domains. There is no evidence that in a substantial portion of the children a normal development can be achieved by early interventions. Most research evidence is available for ABA. A minimal necessary intensity of interventions to achieve positive outcomes cannot be derived from literature. There are no valid statements possible as to cost-effectiveness or consequences of these interventions. Effective early interventions may reduce total autism costs in the long run. This may be achieved when the initial high treatment expenditures are more than compensated later if persons with this disorder have better social functioning.